2020
DOI: 10.1039/d0ra00214c
|View full text |Cite
|
Sign up to set email alerts
|

High voltage vacuum-processed perovskite solar cells with organic semiconducting interlayers

Abstract: The effect of n-type interlayers and electrodes on the voltage and stability of fully vacuum-deposited perovskite solar cells is evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Moreover, a faster decay in the efficiency was observed when the PCE was recorded for 12 h under 1 sun illumination. For the devices with the other two ratios (A and B), the PCE and stability were comparable and in line with existing results on planar devices in which they used the same p-i-n configuration, [42] showing around 20% loss in efficiency after 12 h continuous MPP tracking. However, statistically ( Figure S5, Supporting Information), for the solar cells type A, a larger spread of the values was noted.…”
Section: Resultssupporting
confidence: 89%
“…Moreover, a faster decay in the efficiency was observed when the PCE was recorded for 12 h under 1 sun illumination. For the devices with the other two ratios (A and B), the PCE and stability were comparable and in line with existing results on planar devices in which they used the same p-i-n configuration, [42] showing around 20% loss in efficiency after 12 h continuous MPP tracking. However, statistically ( Figure S5, Supporting Information), for the solar cells type A, a larger spread of the values was noted.…”
Section: Resultssupporting
confidence: 89%
“…21,22 Since the demonstration of the first thermally evaporated methylammonium lead mixed halide (iodide/chloride) perovskite solar cell, 23 most of the research on evaporated perovskite solar cells focused on methylammonium lead triiodide (MAPbI 3 ). [24][25][26][27][28][29] It had been recognised already at the early stages of research that evaporation of methylammonium iodide (MAI) is difficult to control and to perform reproducibly, 30 prompting researchers to explore other, MA-free, perovskite compositions for thermal evaporation. Borchert et al reported on the evaporation of formamidinium lead triiodide (FAPbI 3 ) perovskite layers, reaching a PCE of 14.2%.…”
Section: Introductionmentioning
confidence: 99%
“…Thin BCP films as buffer layers can be processed through vacuum or solution. Although there are various number of studies based on BCP layers processed through vacuum [24][25][26][27], the number of studies on solution processed BCP layers is rather limited [28][29][30][31]. In this work, we studied the effect of BCP layers on the performance of perovskite solar cells by changing the BCP concentration, which was prepared by sol-gel method and also, we have studied the effect of spin-coating speed of BCP layers on the performance of perovskite solar cells in p-i-n configuration as ITO/NiOx/MAPbI3/PCBM/BCP/Ag configuration (Fig.…”
Section: Introductionmentioning
confidence: 99%